Predictive Validity of the Snatch Pull Force-Velocity Profile to Determine the Snatch One Repetition-Maximum in Male and Female Elite Weightlifters - Ingo Sandau; Helmi Chaabene; Urs Granacher (Journal of Functional Morphology and Kinesiology, 2021)
Background: The prediction of one repetition-maximum (1RM) performance from specific tests is highly relevant for the monitoring of training in weightlifting. Therefore, this study aimed at examining the predictive validity of the theoretical 1RM snatch (snatchth) computed from the two-point snatch pull force-velocity relationship (FvR2) to determine actual snatch 1RM performance in elite weightlifters. Methods: Eight (three female, five male) elite weightlifters carried out a 1RM snatch test followed by a snatch pull test with loads of 80% and 110% of the previously determined 1RM snatch. Barbell kinematics were determined for all lifts using video-tracking. From the snatch pull barbell kinematics, the snatch pull FvR2 was modeled and the snatchth was calculated. Results: The main findings indicated a non-significant (p = 0.706) and trivial (d = 0.01) mean difference between the actual 1RM snatch performance and the snatchth. Both measures showed an extremely large correlation (r = 0.99). The prediction accuracy of the actual 1RM snatch from snatchth was 0.2 ± 1.5 kg (systematic bias ± standard deviation of differences). Conclusions: This study provides a new approach to estimate 1RM snatch performance in elite weightlifters using the snatch pull FvR2. The results demonstrate that the snatchth-model accurately predicts 1RM snatch performance.